2004
DOI: 10.1097/01.bcr.0000107202.85453.63
|View full text |Cite
|
Sign up to set email alerts
|

Aquacel Ag® in the Management of Partial-Thickness Burns: Results of a Clinical Trial

Abstract: Aquacel Hydrofiber is a moisture retentive topical dressing that has been demonstrated to be safe and efficacious for the management of partial-thickness burns, showing parity for most dressing related aspects to cadaver skin for this indication. Recently, 1.2% w/w silver has been added to the Aquacel Hydrofiber, to create Aquacel Ag. This new material releases silver within the dressing for up to two weeks, and it is this duration that differentiates it from other sustained release silver delivery products in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 21 publications
0
62
0
Order By: Relevance
“…[10][11][12] The antibacterial activity of silver nanoparticles (AgNPs) had been reported against multiple species of bacteria; for example, Escherichia coli ATCC 8739, 13 Staphylococcus aureus ATCC1431, 14 Escherichia fergusonii, and Klebsiella aerogenes ATCC…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] The antibacterial activity of silver nanoparticles (AgNPs) had been reported against multiple species of bacteria; for example, Escherichia coli ATCC 8739, 13 Staphylococcus aureus ATCC1431, 14 Escherichia fergusonii, and Klebsiella aerogenes ATCC…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is the responsibility of health professionals to choose between passive (inert) bandages and bandages with active principles. In cases of burn injuries, silver-based active bandages are more effective coverage because they require less changes and exhibit a prolonged antibacterial effect (25)(26) . According to an international research carried out in 2010 in a burn ICU, the mean daily cost of using silver dressings (ACTICOAT 7 Antimicrobial Barrier Dressing) was AUD$ 120.77 (2) .…”
Section: Discussionmentioning
confidence: 99%
“…Duteille and Jeffery [3] reported the initial application of the glove to be very easy/easy in 87% of cases with reapplication of the glove very easy/easy in 95% of cases. Caruso et al [14] also reported ease of application using AQUACEL ® Ag in the management of partial thickness burns, with 82% reporting very easy to apply and 18% easy to apply.…”
Section: Ease Of Usementioning
confidence: 99%
“…[6,9] In particular, the use of SSD achieved greater flexibility and ROM when compared to AQUACEL ® Ag for burn wounds. [9] Caruso et al [14] found the flexibility excellent to very good in the 82% of patients with 19% reporting average to poor flexibility. Duteille and Jeffery [3] reported that on initial application of the AQUACEL ® Ag glove, flexibility was either good or excellent reporting 83% at 24 h; however, this reduced to 56% at the final evaluation.…”
Section: Flexibility and Range Of Movementmentioning
confidence: 99%